Service quality and students’ satisfaction at higher learning institutions: The competing dimensions of Malaysian universities’ competitiveness - Hanaysha, Jalal R. M.; Abdullah, Haim Hilman; Warokka, Ari (IBIMA Publishing, 2011)
One of important determinants of national competitiveness is the quality of its higher education.This quality comes from the combination of excellent learning process and public satisfaction on the service delivered. Student satisfaction assessment is vital in determining service quality at higher learning institutions (HEIs).To remain competitive, it requires HEIs to continuously acquire, maintain, and build stronger relationships with students.The main purpose of this paper is to evaluate students’ satisfaction on services provided by HEIs. Specifically, the study found significant relationship between the five dimensions of service quality (tangibility, reliability, responsiveness, assurance, and empathy) or SERVQUAL and students’ satisfaction. From 1000 questionnaires being sent out to respondents, 360 responded.The findings generally indicate that the majority of students are satisfied with the facilities provided by universities. Such findings should help universities make better strategic plan as to enhance students’ satisfaction in particular and its overall performance in general.In general,the results indicated that all the five dimensions of service quality were correlated with student satisfaction.